PENGARUH MORALITAS, ASIMETRI INFORMASI DAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN DANA DESA PADA KECAMATAN KROYA KABUPATEN CILACAP - Yulian, Tri Nurindahyanti; Rahman, Kristanti (JURNAL EKONOMI, 2022)
This study aims to determine the effect of morality, information asymmetry, and internal control on the tendency of village fund fraud in Kroya sub-district, Cilacap district. The population of this research is Kroya District, Cilacap Regency. The sampling technique used is purposive sampling, the type of data used is primary data from 51 respondents in 17 sub-districts in Kroya District, Cilacap Regency. The results of this study indicate that: Morality has no effect on the tendency to fraud. Information asymmetry has no effect on the tendency to fraud. Internal Control affects the Fraud Tendency.